The Efforts to Increase New Student Promotion at STIE-Graha Karya Muara Bulian Using the Apriori Algorithm Method: Upaya Peningkatan Promosi Mahasiswa Baru STIE-Graha Karya Muara Bulian Menggunakan Metode Algoritma Apriori - azwar anas (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2021)
The purpose of this study is to determine the STIE-GK Muara Bulian promotion strategy. The author uses a priori algorithm to analyze the data of new students of STIE-GK Muara Bulian in the academic year 2018/2019. A priori algorithm was chosen because of its ability to analyze data that appears simultaneously and repeatedly and data that has accumulated a long time, so it is necessary to use data mining, to gain knowledge. The data that I use is the data of new students STIE-GK Muara Bulian randomly as many as 100. The research method that I use is to manually calculate data then a trial of the Weka data mining software is conducted. The results of this study indicate, partially Vocational High School and TKJ majors are the most contributors to new students with a confidence level of 13%. The SMK and ADM majors are the second largest contributor to new students with a confidence level of 10%. The management study program comes from the TKJ major with a confidence level of 7%. The accounting study program comes from the TKJ major with a confidence level of 5%.